ANALISIS HUKUM TERHADAP AKTIVITAS PELAYARAN DI KAWASAN ALKI DI TINJAU DARI HUKUM INTERNASIONAL - sendo, nadia; Arman, Zuhdi (LPPM Universitas Putera Batam, 2021)
Considering that the State of lndonesia is the largest archipelagic country, therefore lndonesia is obliged to realize an interest of the international community in the shipping section through sea lanes in the lndonesian archipelago, due to the important role of the State, obliges lndonesia to closely monitor violations that may occur. This study aims to determine shipping activities in the marine waters of the lndonesian archipelago. This type of research in empirical form is also carried out in the form of field research, the type of data taken is of course primary which is obtained through interviews and questionnaires. committing acts that violate the law in accordance with government regulations number 37 of 2002, and violations that are often carried out in the lndonesian Archipelago Sea Lane are illegal weapons smuggling, drugs transporting illegal immigrants, marine pollution and illegal fishing. The punishment given is in the form of a fine.